RANCANG BANGUN SISTEM PEMBELAJARAN PEGAWAI DENGAN METODE E-LEARNING (Studi Kasus di PT Eisai Indonesia). - Primasari, Dewi; Eosina, Puspa; Mulyana, Asep (Fakultas Teknik dan Sains, Universitas Ibn Khaldun Bogor, 2017)
PT Eisai Indonesia requires better handling of the training system for its employees. Currently direct training in one place is still widely used by the company because this system is still considered effective to transfer the skills and knowledge from the trainer to the trainees. The lack of this system is the difficulty of training for employees who are far from the headquarters. So the developed of a webbased distance learning system equipped with online examination is needed as a benchmark of employee understanding of a training. This system development method refers to the waterfall method that starts from the stage of requartment analysis, design system, the stage of writing program code and the program testing phase. The benefits of this research are to facilitate the company in knowing the employee's understanding of a training, to speed up a training understood by the employee, to reduce the cost of visit and the time needed to do the training and improve the quality of exam result.